COVID-19 infection in patients with sarcoidosis: susceptibility and clinical outcomes. Issue 5 (September 2021) - Kahlmann, Vivienne; Manansala, Michael; Moor, Catharina C.; Shahrara, Shiva; Wijsenbeek, Marlies S.; Sweiss, Nadera J.
Abstract : Purpose of review: Patients with sarcoidosis may be at higher risk of coronavirus disease-19 (COVID-19) as over 90% of the patients have pulmonary involvement and many are treated with immunosuppressive agents. This review will summarize the current literature regarding sarcoidosis and COVID-19, with a particular focus on susceptibility, clinical outcomes, management, and approach to vaccination. Recent findings: Data about COVID-19 and sarcoidosis include a number of case series and reports, cohort studies, and registries. Literature is not conclusive whether patients with sarcoidosis have increased susceptibility to COVID-19. Patients with moderate to severe impaired pulmonary function may be at increased risk of adverse outcomes and mortality. Whether immunosuppressive medication increases risk of COVID-19 severity or affects vaccination response is not yet clear. Novel approaches, such as telemedicine and home monitoring programs, are promising to ensure continuity of care for patients with sarcoidosis during the COVID-19 pandemic. Summary: Current evidence about the risk and clinical outcomes of COVID-19 infection in patient with sarcoidosis, is mainly extrapolated from other immune-mediated diseases. Hence, further research that focuses on the sarcoidosis population is warranted.